2015
DOI: 10.1177/0300985815603432
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Cyclin D1, Cytokeratin 20, and Uroplakin III in Proliferative Urinary Bladder Lesions Induced by o-Nitroanisole in Fischer 344/N Rats

Abstract: o-Nitroanisole is an intermediate in the manufacture of azo dyes. In a National Toxicology Program stop-exposure study, o-nitroanisole induced hyperplasia, papillomas, and papillary carcinomas in the urinary bladder of Fischer 344/N rats. o-Nitroanisole was investigated since occupational or environmental exposure to aniline and azo dyes is a risk factor for urinary bladder cancer in humans. The current study describes the morphology of urinary bladder neoplasms seen in rats with respect to those observed in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[4][5][6] Moreover, the following molecules that are still under investigation have been reported to be associated with urinary carcinogenesis: BLCA-4, cytokeratin, fibronectin degradation products, uroplakins and their glycovariants, psoriasin, zinc-alpha-2-glycoprotein, pro-matrix metalloproteinase-2 (proMMP-2), matrix metalloproteinase-7 (MMP-7), and endostatin. [7][8][9][10][11][12][13] It has also been reported that the serum levels of CYFRA 21-1 and soluble E-cadherin are associated with advanced and high-grade urothelial bladder carcinoma. 14,15 In the opinion of Goodison et al, most of these biomarkers may be more useful as prognostic factors aiding therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Moreover, the following molecules that are still under investigation have been reported to be associated with urinary carcinogenesis: BLCA-4, cytokeratin, fibronectin degradation products, uroplakins and their glycovariants, psoriasin, zinc-alpha-2-glycoprotein, pro-matrix metalloproteinase-2 (proMMP-2), matrix metalloproteinase-7 (MMP-7), and endostatin. [7][8][9][10][11][12][13] It has also been reported that the serum levels of CYFRA 21-1 and soluble E-cadherin are associated with advanced and high-grade urothelial bladder carcinoma. 14,15 In the opinion of Goodison et al, most of these biomarkers may be more useful as prognostic factors aiding therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%
“…24 Rat studies with carcinogen induction of bladder neoplasia have also shown a graded increase in urothelial expression of cytokeratin 20, uroplakin III, and nuclear cyclin D1 within the full thickness of the urothelial lining in the context of flat urothelial hyperplasia, although these have not been recommended for routine clinical use in this setting. 25 Given the limited nature of these lesions, studies that maintain tissue architecture in the analysis process and that undertake longitudinal analysis to identify subsequent neoplasia are needed.…”
Section: Discussionmentioning
confidence: 99%